Bactérias promotoras de crescimento para soja em terras baixas - Silva, Isledi William da (2022)
The world population is rising exponentially, which in turn raises the demand for food proportionately. However, sustainable food production must be scaled up, and the reduction of non-renewable fertilizers needs to be rethought. As an option, bacteria capable of promoting growth and biosolubilizing nutrients that already exist in the soil can be used. The aim of this research is to evaluate the use of phosphate biosolubilizing bacteria in lowland soybean crop. The experiment was carried out in a randomized block design with four replications. The treatments distributed in a bifactorial, in which the first factor represents the co-oculation of Bradyrhizobium spp with the following bacteria: (i) Azospirillum spp; (ii) Pseudomonas fluorescens; (iii) Bacillus subtilis; (iv) Bacillus subtilis + Bacillus megaterium; (v) Azospirillum spp + Pseudomonas fluorescens; (vi) Azospirillum spp + Bacillus subtilis; (vii) Azospirillum spp + Bacillus subtilis + Bacillus megaterium; (viii) Azospirillum spp + Pseudomonas fluorescens + Bacillus subtilis + Bacillus subtilis + Bacillus megaterium, and (ix) Witness without the use of bacteria in inoculation. The second factor was tested as phosphate fertilizer doses (0, 50, 100, 150 kg of P2O5 ha-1). The number of plant-1 nodules, plant-1 nodule mass, thousand-grain mass, yield, tissue analysis and bacterial solubilization capacity in the laboratory were measured. The present study highlights the specificity of bacterial genera in promoting associations with the plant and producing different responses of agronomic interest. The bacterium Pseudomonas fluorescens increased the phosphorus content in the plant tissue of soybean by 232% when compared to the control, which can be indicated for an increase in organic phosphorus in the soil through the crop residues left in the soil during a mechanized harvest. The higher soybean yield for the field experiment due to the use of co-oculation of the bacteria Bradhiryzobium, Bacillus megaterium and Bacillus subtillis with the use of 150 kg ha-1 of P2O5, providing biosolubilization of the phosphorus contained in the soil, or even the phosphorus made via fertilizer in sowing soybeans. As bacteria when tested in the laboratory, formation of a solubilization halo in a liquid medium, where a Bacillus bacterium is subtilized as a phosphorus biosolubilizing medium, and as Bacillus subtilis, Bacillus megaterium and Pseudomonas fluorescens, a class with low biosolubilization potential.